(untitled) (Colombia Medica, 2007)
Introduction: It agrees to specify that the nerves are an old biomedical taxonomy of the disease, whose slight knowledge has been elaborated in popular contexts. Today, it is a present disease in many western societies that express a way of the suffering. Objective: This study is centered in exploring the impact of 11-S in the nerves of the Mexican immigrants who live in the United States. Methodology: It is directed by the tradition of the anthropology of the disease. It leans in the original materials, collected in the park of the mountain (Illinois, the United States). The field work was lead from September of 2001 to February of 2002 between users of the «Latin Program» of the Agency «service of the family of South Lake County». The data come from interviews gathered in depth to qualified informers. Three main dimensions were considered in the methodology and work plan. First, episode of the towers’s impact in every day life of Mexican immigrants, the way in which their health was affected, and how the nerves were originated and declared. Secondly, it considers of particular form some questions like the uncertainty on their future and the fear, bound not only to the possibilities of new attacks but also related to the internal changes and the federal policies. At a third moment, it was explored how the Mexican identity was redefined as a result of the attack. Results: They offer the data that the nervous suffering between Mexican immigrants regarding political violence basically does not defer from the manifestations and etiological theories indicated by numerous authors in relation to diverse social groups, cultural and ethnic in previous works. Conclusions: It express the importance of the social context and political generated from the attacks it worsens the experiences of nerves between the Mexican population. In short, the sensation of imminent danger does not only reveals the fear to new terrorist acts but the consequences are also repeated that the decision of the country entails to initiate combat operations.